2017
DOI: 10.21859/hums-23043
|View full text |Cite
|
Sign up to set email alerts
|

Factors Delaying Hospital Arrival Aftr Acute Stroke Onset

Abstract: Introduction: Optimal time of referral after stroke and the use of new therapies, such as r-tPA and blood pressure control, could accelerate symptoms recovery after stroke. The aim of this study was to investigate factors contributing to the delay in referral to hospitals after the occurrence of acute stroke. Methods: This analytic-descriptive study included 425 patients, who had referred to the Hamadan Farshchian hospital during years 2015 and 2016. Demographic data, time of referring to medical center, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
4
4
0
Order By: Relevance
“…In the study of Ghiasian et al in Hamadan, Iran, the time of symptoms initiation to arrival to the hospital was 282 minutes and it was 192 minutes in the study of Griesser et al (24,25), which is close to our results. However, it was 916 minutes in the study of Ayromlou et al, in Tabriz, Iran, which is inconsistent with our study (20).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the study of Ghiasian et al in Hamadan, Iran, the time of symptoms initiation to arrival to the hospital was 282 minutes and it was 192 minutes in the study of Griesser et al (24,25), which is close to our results. However, it was 916 minutes in the study of Ayromlou et al, in Tabriz, Iran, which is inconsistent with our study (20).…”
Section: Discussionsupporting
confidence: 89%
“…In line with our study, the results of studies performed in Europe, America, and Asia indicated that lack of awareness of stroke symptoms, patients' misconceptions and beliefs regarding the primary symptoms, and failure to consult a person after the onset of the symptoms led to further delay in arrival to the hospital and time-to-treatment for stroke patients (22,24,(26)(27)(28)(29)(31)(32)(33). The ndings suggest that consulting with others following the onset of symptoms may be effective in preventing a delay in cases the patient's symptoms are not well recognized or taken seriously.…”
Section: Discussionsupporting
confidence: 87%
“…Along with our study, Ghiasian et al in a study in Hamadan (Iran) reported that the time of symptoms onset to arrival to the hospital was 282 minutes, while it was 192 minutes in the study of Griesser et al (24,25). Nevertheless, in the study of Ayromlou et al in Tabriz (Iran), this time was 916 minutes, which is not in line with our results (20).…”
Section: Discussionsupporting
confidence: 80%
“…However, according to the results of a study by Raty et al, only 5.6% of the patients were referred to the clinics at the desired time (17). In Iran, according to study by Ghiasian et al, the mean delay time was 7.4 hours (18).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, various global studies have been conducted with an educational approach to raise the level of awareness of the community about the warning signs of stroke and the need for early referral of patients after the onset of symptoms (19)(20)(21)(22)(23)(24). In Iran, only few descriptive relevant studies have been conducted to address the causes of delay (18,25), and also no interventional study to increase the public awareness was found. Therefore, this study was conducted due to the importance of this subject and limited relevant studies.…”
Section: Introductionmentioning
confidence: 99%